Traceless Directing Group Assisted Cobalt‐Catalyzed C−H Carbonylation of Benzylamines. Issue 21 (20th September 2017) - Ling, Fei; Ai, Chongren; Lv, Yaping; Zhong, Weihui
Abstract: The first example of cobalt‐catalyzed C( sp 2 )−H carbonylation of benzylamines using a traceless directing group is reported, which was successfully applied to the synthesis of N −unprotected iso‐indolinones through direct C−H/N−H bonds activation. This protocol tolerates a variety of functional groups and provides a facile and efficient method for the formal synthesis of (+)‐garenoxacin. Abstract :